Adsorption removal of cyclopentanol generated from Fenton oxidation treatment industrial wastewater process with activated carbon fiber cloths. Issue 1 (November 2020) - Deng, Lin; Wang, Qing; Zhang, Jianzhu; Ma, Liyuan; Pan, Qian; Hu, Xuemei; Chen, Chen; Zhang, Huiyuan
Abstract: Cyclopentanol (CPL) is an oxidation by-product in the industrial wastewater treatment process with Fenton advanced oxidation technology, which can not be further degraded into CO2 and H2 O by adjusting the dosage of Fenton's reagents. The enormous CPL generated in wastewater would have a serious effect on the chemical oxidation demand (COD) in the effluent quality. The adsorption removal of CPL onto activated carbon fiber cloth (ACFC) was investigated. Based on study of adsorption isothermal, kinetics, thermodynamics, pH, ACFC dosage experiments, the adsorption removal characteristics of ACFC were determined. The results showed that the Langmuir isotherm model describes well the equilibrium process. The removal capacities of CPL on ACFC are 36.1∼63.0 mg g-1 at 303∼313 K. The adsorption behavior of CPL on ACFC is more fitted by the pseudo-second-order kinetic model. The thermodynamic analysis revealed that the adsorption reaction was an exothermic chemisorption process. The effect of pH and adsorbent dosage on CPL adsorption removal were also studied. The results presented in this work will be helpful to the removal of CPL for industrial wastewater treatment process especially that advanced oxidation technology was adopted.